Fattal, M. (2016). Du Bien et de la Crise. Platon, Parménide et Paul de Tarse. Paris, l’Harmattan - Funari, Pedro Paulo (Revista Archai, 2017)
FUNARI, Pedro Paulo A. (2017). Review: Fattal, M. (2016). Du Bien et de la Crise. Platon, Parménide et Paul de Tarse. Paris, l’Harmattan,